Territorial and decolonial alternative: the community radio stations in Michoacán, Mexico - Olmedo Neri, Raul Anthony (2023)
The article analyzes community and indigenous radios in Michoacán to propose that these projects have a decolonial and territorial essence. It builds a theoretical framework based on alternative communication and communicative citizenship concepts and broadens their definitions to apply them to the proposed areas. The methodology included a documentary and spatial review to map community radios in Michoacan and analyze their relevance in the face of digital gaps in the rural locations where they operate. The results show that, located in rural communities with a considerable digital divide that restricts internet access and coverage, these radios position themselves strategically in the area's media ecosystem. The article concludes that these projects are relevant for rural locations because they reduce inequalities in information and communication.